PENGARUH PENDIDIKAN KESEHATAN TERHADAP TINGKAT PENGETAHUAN ORANG TUA TENTANG GIZI ANAK USIA SEKOLAH MELALUI MEDIA POSTER : THE EFFECT OF HEALTH EDUCATION ON THE LEVEL OF PARENTAL KNOWLEDGE ABOUT THE NUTRITION OF SCHOOL-AGE CHILDREN THROUGH MEDIA POSTER - Aprilia Nuryanti; Kusuma, Ratna (Intan Husada : Jurnal Ilmiah Keperawatan, 2023)
Background. School age is the age when growth and development is very rapid so that it requires good nutrition so that the growth and development of the body is balanced. The role of parents is very influential on the growth and development of children which will also affect the nutritional state of children. One of the efforts to overcome the incidence of under or over-nutrition of children is through increasing the level of knowledge of parents by increasing understanding regarding the nutrition of school-age children through health education. Provision of health education to parents about the nutrition of school-age children must use appropriate means and methods in order to attract attention so that they can easily absorb the information provided. One of the methods and media used is lectures using media poster.Purpose. To determine the effect of health education on the level of parental knowledge about the nutrition of school-age children through media poster.Methods. The research method uses pre-experimental with one group pre-posttest design. Respondents amounted to 129 parents of elementary school students. Sampling used in this research is total sampling.Result. The effect of health education on the level of parental knowledge about the nutrition of school-age children through media poster shows that the research respondents before carrying out health education on the nutrition of school-age children had an average value of 6.71 and after carrying out health education on the nutrition of school-age children had an average value of 10.88. Statistical test results using the Wilcoxon test value = 0.000.Conclusion. There is an effect of health education on the level of parental knowledge about the nutrition of school-age children through media poster.